(untitled) (Revista de Investigaciones Universidad del Quindío, 2023)
Infections associated with health care, and specifically device-associated infections, more frequent in intensive care units, are an increasingly frequent problem with a global impact. Therefore, in countries with high economic income, studies are carried out describing the most frequent type of flora, they also know their resistance profiles, and based on this they prepare their management protocols and decide to start empirical antibiotics. In Latin America, there is little information collected on its prevalence and clinical impact, as well as very little or no literature on this type of infection in the department of Quindío, Colombia. Therefore, there is no detailed description of the bacterial profiles nor their resistance profiles; the recommendations that govern in-hospital behaviors are based on foreign studies, without knowing for sure if it can be extrapolated to our population. Due to this, a descriptive study was carried out, reporting cases of infections associated with health care, specifically, infections associated with devices in a general intensive care unit of a third-level clinic in the city of Armenia, Quindío in the period from June to December 2021, finding the most prevalent bacterial agents in this unit, as well as their resistance profiles based on the cultures where they were isolated. Genetic studies were unavailable on these isolated infectious agents, since there is no evidence that they have been carried out in the institution.